Pattern of electrolyte profile among admitted children (1-18 years) at the University of Calabar Teaching Hospital, Nigeria. - Ekpe E. L; Uhegbu K. O.; Orji I. K.; Uhegbu V. M.; Osuji K. C.; Ejikem Eke C. M. (Medico Research Chronicles, 2020)
Background: Electrolyte imbalances among children, if not well managed, have deleterious effects that can lead to increased mortality and morbidity. This study takes into consideration the pattern and profile of electrolyte imbalance among children aged 1-18 years that were admitted for various ailments over a six month period at the University of Calabar Teaching Hospital in Southern Nigeria. Method: This observational study was done at the University of Calabar Teaching Hospital (UCTH). Children aged 1-18 years who were admitted for more than 24hours for various ailments were investigated for electrolytes over a 6-month period. All patients on electrolyte therapy were excluded from the study. Also, patients with congenital or acquired electrolyte abnormalities were excluded from the study. Results were obtained daily for each patient after collecting blood into the appropriate sample bottles. Various values of electrolyte obtained were compared with the reference intervals to ascertain the level of deviation from the expected normal for age. Results: A total of 227 children participated in the study which was made up of 108(47.6%) males and 119(52.4%) females in the ratio 0.9:1.Children aged 1-5 years made up of a bulk of the study population accounting for 55.9%. The study showed that the commonest electrolyte abnormality detected by the studied population was a low level of bicarbonate accounting for 52.9% of all the children. Children aged 1-5 years accounted for 34.8% of children with low bicarbonate levels. Children aged 6-12 years were 11.9%, and those aged 13-18years were 6.2%. Hyponatremia was the next commonest type of electrolyte abnormality in the children, accounting for 39.6% of all sodium abnormalities in the study population.54.6% had normal sodium level and 3.1% had mildly elevated sodium levels. Again, the children aged 1-5 years old had the higher prevalence of hyponatremia (22.9%). Thus, the group of children aged 1-5 year had both the commonest electrolyte abnormalities for both low bicarbonate levels and low hyponatremia. In relation to other age groups, the difference was statistically significant at p value of 0.017. Conclusion: Just like in adults, electrolyte imbalances are common clinico –laboratory presentations with varied manifestations. Therefore, adequate attention should be drawn to these clinical features to properly manage the patients with such presentations.